Study of the dynamics for gas accumulation in the annulus of production wells - Kamil R. Urazakov; Viktor V. Belozerov; Bulat M. Latypov (Записки Горного института, 2021)
Accumulation of associated petroleum gas in the annulus is one of the negative factors that impede the intensification of mechanized oil production. An increase in annular gas pressure causes growth of bottomhole pressure, a decrease in back pressure to the formation and the inflow of formation fluid. In addition, accumulation of gas in the annulus leads to displacement and a decrease in the liquid level above the submersible pump. Insufficient level of the pump submersion (rod or electric submersible) causes a number of complications in the operation of mechanized production units associated with overheating of the elements in pumping units. Therefore, the development of technologies for optimizing the gas pressure in the annulus is relevant. Method for calculating the intensity of gas pressure increase in the annulus of production wells operated by submersible pumps has been developed. Analytical dependence for calculating the time interval of gas accumulation in the annulus, during which the dynamic level decreases to the pump intake, is obtained. This value can be used to estimate the frequency of gas withdrawal from the annulus using compressors. It has been found that the rate of increase in annular gas pressure in time increases non-linearly with a rise in the gas-oil ratio and a decrease in water cut, and also linearly increases with a rise in liquid flow rate. Influence of the operating (gas-oil ratio) and technological (value of the gas pressure maintained in the annulus) factors on the flow rate of the suspended reciprocating compressor driven by the beam engine, designed for forced withdrawal and redirection of the annular gas into the flow line of the well is analyzed.